Corporate response to the Black Lives Matter movement: determinants of speaking out in support of social causes - Chen, AJ Yuan; Dechow, Patricia M.; Tan, Samuel T. (Review of Accounting Studies, 2026)
We document that firms vary in their timeliness of support for the Black Lives Matter (BLM) movement following the death of George Floyd in May 2020, and that timeliness is an indicator of authenticity. We predict that firms that speak out quickly in support of BLM (via Twitter or their websites) have made more investments in diversity and inclusion, relative to firms that speak out slowly (via conference calls or annual reports) or that remain silent. Consistent with this prediction, quick -disclosing firms have greater workforce diversity, have boards with greater ethnic diversity, and are more likely to tie executive compensation to diversity and inclusivity. Furthermore, quick -disclosing firms increase their hiring of both Black American employees and Black directors relative to firms that stay silent. We also document that quick-disclosing firms are part of more supportive stakeholder networks. We develop an inclusivity index and show that firms with higher index levels are more likely to speak out on the Capitol Riots, the Asian Spa Shootings, and voting rights.